How export-led growth can lead to take-off - Maximilian Benner (Leuphana Universität Lüneburg, Institut für Volkswirtschaftslehre, 2011)
Export-led growth has gained considerable prominence as a model for economic development since its use by East Asian newly industrializing countries. Thus, the question of how it can be used by other countries wishing to industrialize and under what circumstances it can lead to the take-off of an economy is highly relevant for development policy. In light of current macroeconomic imbalances on the global stage, the question of sustainability arises: Is take-off by export-led growth possible without permanent balance-of-trade surpluses? The article gives a brief overview and offers thoughts into various ways in which the impetus of exportled growth for the overall economy might work.
Keywords: 330; Exportinduziertes Wachstum; Entwicklung; Entwicklungsländer